Cirsimaritin inhibits influenza A virus replication by downregulating the NF-κB signal transduction pathway - Yan, Haiyan (Virol J, 2018)
BACKGROUND: Artemisia scoparia Waldst and Kit is a famous traditional Chinese medicine widely distributed in Xinjiang, China. Flavonoids extracted from it exhibits inhibitory activities against several influenza virus strains. Despite this fact, the antiviral properties of CST, one of such flavonoids, against the influenza virus has not been reported. Thus, the aim of this study is to investigate the anti-influenza virus efficacy and antiviral mechanism of CST. METHODS: The inhibitory activity of CST against influenza viruses was assessed by using viral titers and performing Western blot, qRT-PCR, and immunofluorescence assays in Madin–Darby canine kidney (MDCK) cells and a human monocytic cell line (THP-1). The mechanism of CST against influenza virus was analyzed by hemagglutination inhibition (HI) assay, neuraminidase (NA) inhibition assay, and Western blot. RESULTS: CST reduced viral titers and influenza A virus (IAV) RNA and protein synthesis in a dose-dependent manner. Mechanistically, CST had no inhibitory effect on the attachment and release processes of the viral life cycle, as indicated by the HI and NA assays. Conversely, the CST-mediated inhibition of IAV is possibly linked to the inactivation of the NF-κB/p65 signal pathway. CST also suppressed the activation of JNK MAPK and P38 MAPK in vitro. In line with NF-κB/p65 inhibition, the expression levels of proinflammatory cytokines (TNF-α, IL-1β, IL-8, and IL-10) and the inflammation-related protein COX-2 were downregulated by CST. CONCLUSIONS: CST inhibited IAV replication by downregulating the NF-κB signal transduction pathway. CST may be a potential agent or supplement against IAV infection.